Influence of Temperature and Electrolyte Concentration on the Structure and Catalytic Oxygen Evolution Activity of Nickel–Iron Layered Double Hydroxide. Issue 52 (21st August 2018) - Andronescu, Corina; Seisel, Sabine; Wilde, Patrick; Barwe, Stefan; Masa, Justus; Chen, Yen‐Ting; Ventosa, Edgar; Schuhmann, Wolfgang
Abstract: NiFe layered double hydroxide (LDH) is inarguably the most active contemporary catalyst for the oxygen evolution reaction under alkaline conditions. However, the ability to sustain unattenuated performance under challenging industrial conditions entailing high corrosivity of the electrolyte (≈30 wt. % KOH), high temperature (>80 °C) and high current densities (>500 mA cm −2 ) is the ultimate criterion for practical viability. This work evaluates the chemical and structural stability of NiFe LDH at conditions akin to practical electrolysis, in 30 % KOH at 80 °C, however, without electrochemical polarization, and the resulting impact on the OER performance of the catalyst. Post‐analysis of the catalyst by means of XRD, TEM, FT‐IR, and Raman spectroscopy after its immersion into 7.5 m KOH at 80 °C for 60 h revealed a transformation of the structure from NiFe LDH to a mixture of crystalline β‐Ni(OH)2 and discrete predominantly amorphous FeOOH containing minor non‐homogeneously distributed crystalline domains. These structural and compositional changes led to a drastic loss of the OER activity. It is therefore recommended to study catalyst stability at industrially relevant conditions. Abstract : Abundant non‐noble metal catalysts exhibiting high stability and high catalytic activity towards the oxygen evolution reaction (OER) are required to improve alkaline water electrolysis. Laboratory tests usually are performed at gentle conditions as compared with those in industrial environment. Chemical transformation of nickel–iron layered double hydroxide (NiFe LDH) in highly concentrated alkali solution at high temperature is reported and the impact on the catalytic OER activity is discussed.